A hora e a vez de Augusto Matraga: do humano ao mítico - Toledo, Marleine Paula Marcondes e Ferreira de (Revista do Instituto de Estudos Brasileiros, 1988)
This paper shows how Guimarães Rosa arrives at universal images through the use of regional images (i. e.: cangaço). The core of this micro-narrative - whose theme is the union of opposites - places Matraga in contact with his divine world. The ternary structure which is commom to many hagiographies brings to the fore the character's inner conflicts between Good and Evil, as he lives out three phases: the mythic, the social, and the human. A mandala image - a circle that closes - which is present in the text helps us understand the character's fate.